2002
DOI: 10.1159/000055224
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-Up of Patients in Four Prospective Studies of the German Breast Cancer Study Group (GBSG): A Summary of Key Results

Abstract: Evaluation of treatment modalities and prognostic factors in early breast cancer requires a long-term follow-up of patients in prospective studies. The German Breast Cancer Study Group (GBSG) started four nationwide studies in 1983 in which a total of 2,746 patients have been enrolled and followed for about 10 years. Questions that have been addressed in these studies are still relevant today and comprise the role of breast-conserving therapy, the duration of adjuvant chemotherapy, and whether adjuvant radioth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 26 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…2746 patients from 118 clinical institutions entered the studies. The treatment design of the studies is shown in [5], Table 1. The following covariates were registered at primary diagnosis: patient’s age, menopausal status, number of positive axillary lymph nodes, tumour location, tumour size, histologic tumour grade, oestrogen, and progesterone receptor status.…”
Section: Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…2746 patients from 118 clinical institutions entered the studies. The treatment design of the studies is shown in [5], Table 1. The following covariates were registered at primary diagnosis: patient’s age, menopausal status, number of positive axillary lymph nodes, tumour location, tumour size, histologic tumour grade, oestrogen, and progesterone receptor status.…”
Section: Applicationmentioning
confidence: 99%
“…The methods are applied to a dataset containing data from four studies conducted by the German Breast Cancer Study Group (GBSG) see e.g. [5]. …”
Section: Introductionmentioning
confidence: 99%